THE INTERPLAY OF TRAUMA IN COLLEEN HOOVER’S IT ENDS WITH US: A PSYCHOANALYTIC EXPLORATION THROUGH SIGMUND FREUD’S THEORIES - Dapawole, Hildegard Chantika; Restu Arini (Journal of Innovation Research and Knowledge, 2024)
Trauma is a profound emotional and psychological wound resulting from violent or distressing events. It impacts individuals of all ages, leading to long-term effects on behavior and relationships. This study aims to explore the trauma experienced by Lily in Colleen Hoover's It Ends With Us and examine its impact on her behavior and social interactions. Sigmund Freud's psychoanalytic theory as well as neuroses, repression and the compulsion to repeat as supporting theories for types of traumas are used in this study. The method used in this study is a qualitative descriptive method to analyze the data. The data in this study were obtained from conversations, statements and relevant sentences from Lily Bloom in the novel through actions and dialogues. The results of this study indicate that Lily Bloom experienced a combination of acute, chronic and complex trauma. Which affects her psychological and emotional well-being but also her social life that makes it difficult to trust relationships and have social isolation.